Parliamentary elections in Poland in 1935 and 1938 - Górecki, Dariusz (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The article contains a concise discussion of the election issues contained in the constitution of 1935 and in both the 1935 electoral ordinances to the Sejm and the Senate, as well as the analysis of the results of the parliamentary elections held in 1935 and 1938. The low voter turnout in 1935 was caused by the boycotting of the elections by the opposition groups. On the other hand, in 1938, despite the fact that the opposition had announced a boycott of the elections, the turnout in the elections to the Sejm increased by 21.2% and by 7.6% to the Senate. This was caused by an increase of international tension, the incorporation of Zaolzie Silesia into Poland, forcing Lithuania to establish diplomatic relations, as well as an improvement in the economic situation in the country and an increase in investments in industrial districts. Moreover, in every society there is a certain fraction of voters abstaining from voting due to a lack of interest in the political life of the country.